Earth-Air Heat Exchanger Systems for Energy Efficiency Enhancement in Algerian Residential Buildings: A Multi-Climate Zone Analysis - Ben Babba, Khiera; Sellami, Mohammed; Ali, Sellami (International Journal of Computational and Experimental Science and Engineering, 2026)
This study investigates Earth-Air Heat Exchanger (EAHE) systems for improving energy efficiency in Algerian residential buildings across diverse climatic zones. Algeria’s climate conditions, ranging from Mediterranean coastal areas to hot arid desert regions, present unique challenges for passive cooling and heating technologies. This research analyzes EAHE performance in three representative cities: Tamanrasset (hot arid), Constantine (semi-arid Mediterranean), and Adrar (hot desert), using comprehensive meteorological data and building energy simulation models. The study employs mathematical modeling incorporating heat transfer analysis, soil thermal properties, and building energy dynamics. Monthly and hourly analyses used actual climate data with ambient temperatures ranging from 7.5°C to 35.5°C and solar irradiation values from 5.4 to 12.2 MJ/m²/day. The modeled EAHE system consists of 100-meter underground pipes buried at 3-meter depth, serving typical 150 m² residential buildings. Results demonstrate significant energy efficiency improvements across all climate zones. Annual energy savings ranged from 24.2% (Constantine, 1,892 kWh) to 31.3% (Adrar, 3,156 kWh), with Tamanrasset achieving 28.5% reduction (2,847 kWh). EAHE effectiveness values ranged from 65% to 82%, with peak performance during extreme ambient conditions. Hourly analysis revealed 4-8°C temperature reductions at EAHE outlets during peak summer, significantly reducing cooling loads. Economic analysis indicates annual cost savings of 427-473 per household with 6-8 year payback periods, demonstrating economic viability. This research contributes practical guidelines for EAHE implementation in North African residential buildings, supporting earth-coupled heat exchange systems as effective strategies for reducing energy consumption and enhancing thermal comfort in Algeria’s challenging climates.